THE PREVALENCE OF LATEX GLOVES - RELATED COMPLAINTS AMONG DENTAL STUDENT - Iliyana Stoeva (Peytchinski Publishing, 2011)
Latex gloves are a frequent cause of complaints in dental staff, which complaints may start during the student education.The aim of the present study was to evaluate the prevalence of latex gloves-related complaints among dental students and to establish the etiology of these problems.Material and Methods: 122 dental students completed a questionnaire. Those with latex glove-related complaints were evaluated for latex sensitivity by assessment of skin prick test and for cell-mediated sensitivity to rubber additives and occupational hazards by assessment of patch test.Results: 8.2 % of dental students had skin hand complaints wearing latex gloves. 3 of them (30 %) showed a positive skin prick to latex and 1 of them (10 %) showed a positive patch test to rubber additives.Conclusions: Dental students are at risk to develop occupational hypersensitivity although the limited exposure to latex gloves during education.